Pengaruh Good Corporate Governance Terhadap Optimalisasi Aset Perusahaan Perbankan di BEI Tahun 2017-2022 - Andini, Yulia Andini; Nurdiawansyah; Afrizal Nilwan (Owner : Riset dan Jurnal Akuntansi, 2024)
Analysis of the impact of Good Corporate Governance represented by institutional ownership, management ownership, board of directors, board of commissioners, and audit committee, on the optimization of bank assets through the measurement of Return on Asset (ROA) is the purpose of this research. Banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2017-2022 are the population of this study. Multiple linear analysis with purposive sampling as the sample size determination method is the method applied in this research. Based on the conclusion of this research, asset optimization of banking companies listed on the IDX between 2017 and 2022 is significantly influenced by the structure of the board of directors, the membership of the board of commissioners, and the quality of the audit committee. Meanwhile, from 2017 to 2022, asset optimization of banking companies listed on the IDX is not significantly influenced by either institutional or managerial ownership.